2012
DOI: 10.17221/190/2011-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of honey-sweetened soymilk with Bifidobacterium lactis Bb-12 and Bifidobacterium longum Bb-46: fermentation activity of bifidobacteria and in vitro antagonistic effect against Listeria monocytogenes FSL N1-017

Abstract: Slačanac V., Lučan M., Hardi J., Krstanović V., Koceva-Komlenić D. (2012): Fermentation of honey-sweetened soymilk with Bifidobacterium lactis Bb-12 and Bifidobacterium longum Bb-46: fermentation activity of bifidobacteria and in vitro antagonistic effect against Listeria monocytogenes FSL N1-017. Czech J. Food Sci., 30: 321-329.The influence of the honey addition on the fermentative activity of Bifidobacterium lactis Bb-12 and Bifidobacterium longum Bb-46 in soymilk was determined. Additionally, the inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
4
0
2
Order By: Relevance
“…Honey is a functional food with unique ingredients, properties against pathogenic bacteria, and bifidogenic effects. It contains fructooligosaccharides, which act as prebiotics and has various nutrients [14,32]. The preliminary study supported earlier studies that fermented soymilk with 5% honey increased the growth of Lactobacillus casei subsp.…”
Section: Discussionsupporting
confidence: 83%
“…Honey is a functional food with unique ingredients, properties against pathogenic bacteria, and bifidogenic effects. It contains fructooligosaccharides, which act as prebiotics and has various nutrients [14,32]. The preliminary study supported earlier studies that fermented soymilk with 5% honey increased the growth of Lactobacillus casei subsp.…”
Section: Discussionsupporting
confidence: 83%
“…Some researchers also utilized skimmed milk powder to produce yogurt [ 69 , 70 , 76 ]. As for the non-dairy products, kefir [ 74 ], soy milk [ 67 , 80 ], and hydrolyzed soybean extract [ 74 ] were chosen to replace the animal’s milk. The most common starter culture probiotics used to produce yogurt are the S. thermophilus and L. delbrueckii ssp.…”
Section: Prebiotic Properties Of Honeymentioning
confidence: 99%
“…The findings of numerous investigations revealed that the number of probiotics in honey-containing foods is significantly enhanced. Monofloral honey (chestnut, acacia, lime honey) and polyfloral honey (eucalyptus, greenbrier) in yogurt were found to be good prebiotic sources for cultivating Bifidobacteria strains of diverse subspecies [ 67 , 69 ]. Saudi Arabian raw honey [ 68 ], black locust honey [ 71 ], Kerala natural honey [ 72 ], African commercial honey [ 76 ], marjoram honey [ 77 ], and pine honey [ 78 ] were all found to be suitable for cultivating Lactobacillus and Bifidobacterium species in the dairy and non-dairy goods.…”
Section: Prebiotic Properties Of Honeymentioning
confidence: 99%
“…However, Bakr et al (2015) reported a decline in Bifidobacteria population (24 × 10 6 to 10 × 10 6 cfu/g) in bio-yoghurt obtained by culturing with ABT at higher concentration of honey (5 to 15 per cent). An increase in bifidobacterial cells population, a faster decline in pH value and the degradation of principal oligosaccharides (raffinose and stachyose) during fermentation indicated stimulation of growth of B. longum Bb-46 and B. lactis Bb-12 in soymilk containing addition of acacia and chestnut honeys (Slacanac et al , 2012). In another experiment, ABT fermented milk made from mixed cow milk and peanut milk (1:1) containing 4 per cent honey retained highest viable count (cfu/ml) of S. thermophilic (38 × 10 7 ), L. acidophilus (21 × 10 5 ) and Bifidobacterium lactis Bb12 (33 × 10 5 ) after 14 days of storage at 4°C (Abou-Dobara et al , 2018).…”
Section: Growth Characteristics Of Probiotics In Honey Matrixmentioning
confidence: 99%